OPTIMALISASI PENCEGAHAN STUNTING BERBASIS SOSIALISASI DI DUSUN PRANTEN - Tariska Yuli Susanti; Puspa Mutiara Rahayu; Animul Fikrotul Amna; Pinaka Asiva Rachmadani; Afifah Dwi Shopariyani; Nita Amelia Tri Cahyani; Rizki Faishal Fadhil; Muhammad Syafrizal Nur Rahman; Anggara Lintang Wicaksana; M. Erfan Maulana Fajar; Alvin Zuhair (Pusat Penelitian dan Pengabdian Masyarakat, 2026)
Stunting is a growth and development disorder caused by long-term nutritional deficiencies from pregnancy through the first 24 months of life. Stunting affects children's physical growth and their mental, cognitive, and intellectual development. Magelang Regency still has a relatively high stunting prevalence of 19.3 percent in 2024. Of the 72,603 recorded toddlers, 52,460 experienced nutritional problems, including 10,816 stunted children, 33,402 children with low body weight, 5,850 underweight children, and 77 children with severe malnutrition. Stunting cases are most commonly found in mountainous areas. Dusun Pranten is located in the highest area of Mount Telomoyo, resulting in limited access to health services, education, and clean water during the dry season. In addition, most residents work as farmers and livestock breeders, indicating the importance of stunting education for the community. This community service activity aimed to optimize stunting prevention efforts. The method used was action research with a participatory action research model involving posyandu cadres as the main partners. The program was implemented through preparation, implementation, and evaluation stages. Socialization activities were conducted through counseling sessions, interactive discussions, and the distribution of educational media such as presentations and brochures. The results showed increased awareness and understanding among mothers of toddlers regarding stunting and the importance of balanced nutrition. Furthermore, the active involvement of posyandu cadres contributed to improving community participation and program sustainability.